2017
DOI: 10.1016/j.seizure.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the effects of long-term valproic acid treatment on metabolic profiles in newly diagnosed or untreated female epileptic patients: A prospective study

Abstract: Based on the findings of this study, we proposed that VPA induced hypoadiponectinemia which correlates significantly with insulin resistance. These two factors may be responsible for weight gain, possible by stimulating appetite. Valproic acid appears to be use cautionally in obese females with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…Similarly, treatment with VPA predisposed obese children with idiopathic epilepsy to insulin resistance and lower adiponectin levels compared to age and gender matched obese controls [88]. VPA also induced hypoadiponectinemia and insulin resistance in previously untreated people with epilepsy [89,90]. Other studies, however, have found non-significant increases in adiponectin levels after VPA treatment [91,92].…”
Section: 6mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, treatment with VPA predisposed obese children with idiopathic epilepsy to insulin resistance and lower adiponectin levels compared to age and gender matched obese controls [88]. VPA also induced hypoadiponectinemia and insulin resistance in previously untreated people with epilepsy [89,90]. Other studies, however, have found non-significant increases in adiponectin levels after VPA treatment [91,92].…”
Section: 6mentioning
confidence: 99%
“…Low plasma adiponectin levels are associated with obesity and T2DM [83,94]. The degree of hypoadiponectinemia is most closely associated with the degree of insulin resistance and hyperinsulinemia [89,93]. The presence of insulin resistant previously untreated females with epilepsy indicates that weight gain itself may not cause insulin resistance [89], but rather that adiponectin deficiency may promote insulin resistance and weight gain.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…[23], которые проанализировали частоту и степень увеличения МТ, индуцированного приемом ВК в монотерапии у мужчин и женщин, страдающих эпилепсией. Было выявлено более выраженное и частое увеличение МТ у женщин, получавших ВК в монотерапии, по сравнению с мужчинами [27]. Также определили, что увеличение МТ чаще встречается у девочек пубертатного возраста, принимающих ВК [28].…”
Section: влияние пола и возраста пациента на риск вкиндуцированного уunclassified
“…Увеличение экспрессии мРНК adipoR1 в клетках печени, возможно, является благоприятной реакцией, уравновешивающей подавляемую секрецию адипонектина из адипоцитов. Полученные данные соответствуют предыдущим исследованиям [51], показавшим низкую концентрацию адипонектина у пациентов с ожирением и сахарным диабетом 2-го типа, объясняя биологическую связь между избыточной МТ и расстройствами, связанными с ней. Основываясь на результатах, полученных в исследовании H. Sidhu [52], можно предположить, что ВК индуцирует гипоадипонектинемию и это коррелирует с резистентностью к инсулину.…”
Section: влияние вк на адипокиныunclassified